Utilization of Hydrogen Pentoxide and Hydrogen Peroxide in transportation sector: A comprehensive assessment study - Abdurakhmanova, Assem; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
In accordance with the analysis utilizing the GREET datasets, this study establishes three distinct options as a foundational framework for comparing Hydrogen Pentoxide and Hydrogen Peroxide, particularly examining their potential applications for transportation sector. These options are structured based on three primary sources: electricity, natural gas and gaseous hydrogen. The variations in values across these options are attributed to electricity to simplify performance evaluation within the overall framework. These options include various methodologies for electricity generation, covering both non-renewable energy sources, such as coal, natural gas, and oil, and renewable energy sources, such as solar and biomass. A traditional method for producing Hydrogen Peroxide and Hydrogen Pentoxide is also included for comparison. As demonstrated in Option 1 (with coal) for Hydrogen Peroxide, the emission indices are 1.3 kg of CO2 and 3.21 g of CH4.
Keywords: Hydrogen; Hydrogen Pentoxide; Hydrogen Peroxide; Transportation sector; Environmental impact; Energy; Computer Science; Engineering